Musika para sa lahat musika mo, musika ko - Uyehara, Marion Raphael J.; Guadalupe, Jocelyn T. (Quezon City College of Music, University of the Philippines Diliman, 2018)
The project concentrates on the application of music teaching to people with physical disabilities. Ir shows how the role of music strongly affects the lives of these people. Music sessions of the project run within the period of one year that consist of music activities such as singing, instrument playing and dancing. The project is also similarly relatable to music therapy but mainly focuses on the aspect of educational process.
Thesis (B.M. Music) -- University of the Philippines Diliman
Keywords: School music -- Instruction and study